Faktor-faktor yang Mempengaruhi Sikap Perawat dalam Keselamatan Pasien: Systematic Review: Factors Influencing Nurse Attitudes in Patient Safety: Systematic Review - Annisa Rahmi Galleryzki; Rr. Tutik Sri Haryati; Dadan Bardah; Kartika Mawar Sari Sugianto; Endang Sudjiati; Elisabet Herlyani Bota Koten (Journal of Holistics and Health Sciences (JHHS), 2023)
Nurses have a critical role in ensuring care delivery focuses on patient safety and injury prevention during treatment. Positive attitudes toward injury prevention can improve patient safety; however, several factors such as age and work experience are believed to have influenced nurses’ safety attitudes. A systematic review searched data through online databases such as Scopus, ScienceDirect, Wiley Online Library, and EBSCO for articles published between 2010 and 2020. The keywords used were "patient safety attitude AND" nurse "and" patient safety "AND "Nurse attitude" OR "factor analysis." The article selection process used the PRISMA method. The total number of articles obtained was 727, and then only 19 were used in this review after screening. Factors affecting patient safety attitudes are identified into four categories, namely (1) demographic characteristics such as age, genders, educational level, position, work experience, and working unit, (2) physical and psychological exhaustion, (3) obtainable education, and (4) organizational influence. Several factors can cause the nurses negative attitudes towards patient safety, such as burnout and fatigue. Moreover, other factors can make the nurses positive attitudes, such as education, training, and support from the organization. Therefore, efforts are needed to increase knowledge and the organizational influence as well as the management of nurse fatigue and burnout as part of improving nurses' safety attitudes. ABSTRAK Keselamatan pasien digambarkan sebagai upaya untuk mencegah kesalahan medis atau cedera yang dapat dihindari untuk melindungi pasien. Perawat sebagai tenaga kesehatan yang selalu berinteraksi dengan pasien dan tenaga kesehatan lainnya memiliki peran penting dalam memastikan pemberian asuhan berfokus pada keselamatan pasien dan pencegahan cedera selama perawatan pada perawatan jangka pendek maupun jangka panjang. Telaah literature ini mencari data melalui system Scopus, Science Direct, Wiley Online Libarary, dan Ebschoohost untuk artikel yang diterbitkan antara tahun 2010 sampai 2020. Kata kunci yang digunakan adalah “patient safety attitude” OR “patient safety” AND “nurse” OR “nurse attitude”. Total artikel yang didapat adalah 727 kemudian hanya 18 artikel yang digunakan dalam telaah literature ini setelah dilakukan screening. Artikel yang dianalisis terkait dengan factor-faktor yang berhubungan dengan sikap perawat dalam keselamatan pasien. Factor yang mempengaruhi sikap keselamatan pasien teridentifikasi menjadi 4 kategori, yaitu berdasarkan karakteristik perawat, kelelahan fisik dan psikologis, pengetahuan yang didapat, dan organisasi. Beberapa faktor dapat menyebabkan sikap perawat dalam keselamatan pasien menjadi negatif, seperti adanya kelelahan dan burnout. Oleh karena itu diperlukan upaya untuk meningkatkan pengetahuan dan peran organisasi serta pengelolaan kelelahan dan burnout perawat sebagai bagian peningkatan sikap keselamatan perawat.